Comparative Study on Pharmacokinetics of Four Long-Acting Injectable Formulations of Enrofloxacin in Pigs - Ahmad, Salah Uddin; Sun, Jichao; Cheng, Fusheng; Li, Bing; Arbab, Safia; Zhou, Xuzheng; Zhang, Jiyu (Frontiers in Veterinary Science, 2021)
A comparative study on pharmacokinetics of four long-acting enrofloxacin injectable formulations was investigated in 36 healthy pigs after intramuscular injection according to the recommended single dose @ 2.5 mg/kg body weight. The drug concentrations in the plasma were computed using high-performance liquid chromatography (HPLC) with fluorescence detection. WinNonLin5.2.1 software was used to analyze the experimental data and compared it under one-way ANOVA using SPSS software with a 95% confidence interval (CI). The main pharmacokinetic parameters i.e. the maximum plasma concentrations (Cmax), the time to maximum concentration (Tmax), area under the time curve concentration (AUCall) and Terminal half-life (T1/2) were 733.84±129.87, 917.00±240.13, 694.84±163.49, 621.98±227.25 ng/ml, 2.19±0.0.66, 1.50±0.37, 2.89±0.24, 0.34±0.13 hours, 7754.43±2887.16, 8084.11±1543.98, 7369.42±2334.99, 4194.10±1186.62 ng h/ml, 10.48±2.72, 10.37±2.38, 10.20±2.81, and 10.61±0.86 hours for 10% enrofloxacin (Alkali), 20% enrofloxacin (Acidic), Yangkang and control drug Nuokang® respectively. There were significant differences among Cmax, Tmax, and AUCall of three formulations compare with that of the reference formulation. No significant differences were observed among the T1/2 for tested formulations compare with the reference formulation. The pharmacokinetic parameters showed that the tested formulations were somewhat better compared to the reference one. The calculated PK/PD indices were effective for bacteria such as Actinobacillus pleuropneumoniae and Pasteurella multocida with values higher than the cut-off points (Cmax/MIC90≥10-12 and AUC/MIC90 ≥125). However, they were not effective against bacteria like Haemophilus parasuis, Streptococcus suis, E. coli, and Bordetella bronchiseptica where lower values were obtained.